Plan de negocios proyecto inmobiliario El Rosal ubicado en El Valle de los Chillos, cantón Rumiñahui, sector Santa Clara - Criollo Mendoza, Gabriela Raquel (2021)
In this degree work, the business plan of the real estate project El Rosal, located in the valley of Los Chillos, canton Rumiñahui, Santa Clara sector, was developed through the methodological analysis of macroeconomic variables, the analysis of the sector, competition, and real estate market conditions, in addition to the analysis of supply and demand, which allowed the approach of market strategies…